Developing a Curriculum Synchronisation Model to Increase the Effectiveness of Competency-Based Learning - Ferunika Ferunika; Agus Pahrudin; Yuberti Yuberti; Achi Rinaldi; Aditia Fradito (Yayasan Letiges Konsultan Sosial, 2026)
This study aims to develop and evaluate a curriculum synchronisation model between formal and non-formal education to optimise competency-based learning at the secondary school level. The research was motivated by the need to bridge the gap between competencies taught in schools and the skills required in the labour market and society. A mixed-methods approach with a sequential explanatory design was employed. Quantitative data were collected using purposive sampling through questionnaires distributed to 220 respondents, consisting of secondary school teachers, non-formal education managers, and students involved in integrated learning programs. In contrast, qualitative data were obtained through in-depth semi-structured interviews and non-participant classroom observation. Data were analysed using descriptive-inferential statistics and thematic analysis, while the validity of findings was ensured through methodological and source triangulation supported by expert judgment. The findings indicate that the implementation of the synchronised curriculum model increased students' overall competencies by 17%, with the most significant improvement observed in the psychomotor domain. Furthermore, 87% of respondents agreed that collaboration between formal and non-formal education is essential to enhance the relevance of learning. The study concludes that curriculum synchronisation effectively integrates theoretical and practical learning, strengthens institutional collaboration, and supports the implementation of competency-based education. These findings contribute theoretically to the development of integrative curriculum design and offer practical implications for adaptive and sustainable national education policies. However, this study is limited by its relatively short implementation period and its focus on a specific regional context, which may affect the generalizability of the findings.